2020
DOI: 10.3174/ajnr.a6505
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Study of Thyroid Ultrasound for Predicting BRAF Mutation in Papillary Thyroid Carcinoma: Preliminary Results

Abstract: BACKGROUND AND PURPOSE: It is not known how radiomics using ultrasound images contribute to the detection of BRAF mutation. This study aimed to evaluate whether a radiomics study of gray-scale ultrasound can predict the presence or absence of B-Raf proto-oncogene, serine/threonine kinase (BRAF) mutation in papillary thyroid cancer. MATERIALS AND METHODS: The study retrospectively included 96 thyroid nodules that were surgically confirmed papillary thyroid cancers between January 2012 and June 2013. BRAF mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Since the introduction of radiomics, many studies concluded that it has potential power for analyzing thyroid cancers, including the differentiation between malignant and benign nodules or the prediction of prognosis or gene mutations in papillary thyroid carcinoma [ 12 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, little is known about the association of radiomics and FTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of radiomics, many studies concluded that it has potential power for analyzing thyroid cancers, including the differentiation between malignant and benign nodules or the prediction of prognosis or gene mutations in papillary thyroid carcinoma [ 12 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, little is known about the association of radiomics and FTC.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to tomographic images, US has several limitations in quantitative analysis including uncommon 3D data available, lack of reproducibility, lack of representative features due to limited amount of image data, operator dependency, and dependency on US machines. However, US is the most widely used standard imaging tool for evaluating thyroid pathology and many recent studies concluded that quantitative features extracted from thyroid US images have favorable results [ 12 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if we can predict genes mutated in thyroid cancer through convenient and feasible approaches, this information would contribute to improving tumor diagnosis, judging the prognosis, and personalizing the treatment. To date, two studies have applied radiomics to estimate BRAF mutations in PTC patients [ 73 , 81 ]. These two studies offered a consistent outcome that ultrasound radiomics has a limited value in predicting BRAF nutation.…”
Section: Radiomics In Thyroid Cancer Predictionmentioning
confidence: 99%
“…In fact, to this date, several studies [ 7 , 20 , 28 , 43 ] recommend that the lesion evaluation should be achieved from a combination between the clinician evaluation and ML or DL outcome. Moreover, it is worth noticing that most AI-based studies focused on thyroid pathologies are performed using retrospectively collected data [ 9 , 11 , 33 , 40 , 42 , 51 , 55 , 60 , 61 , 62 , 63 , 65 , 66 , 67 ]. Conversely, studies that prospectively evaluate AI predictive models concerning thyroid disease diagnosis are limited in the literature [ 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, [ 42 , 60 , 61 ] implemented radiomics models that analyze the risk stratification and predict the aggressiveness of the thyroid carcinoma with high values of accuracy, i.e., roughly 85 percent. Radiomics analysis has the potential to determine tumor phenotypes or the presence of gene mutations [ 62 , 63 ]. Furthermore, several studies have investigated by means of radiomic features the occurrence of metastases [ 64 ] or disease-free survival [ 65 ].…”
Section: Ai and Radiomics In Thyroid Diseasesmentioning
confidence: 99%